The Effect of a Climate Change Monitoring Program on Students' Knowledge and Perceptions of STEAM Education in Korea - Jeong, Sophia; Kim, Hyoungbum (Eurasia journal of mathematics, science and technology education, 2015)
Korea has recently started to implement a STEM-like approach in K-12 education, titled STEAM (Science, Technology, Engineering, Arts, and Mathematics) curriculum, to educate the next generation of students to become creative innovators. As this approach has been shown to increase educational success, it is vital to prepare and develop interest in middle school students to participate in STEAM subjects-related learning opportunities. This study examined the impact of hands-on global climate change monitoring projects whose curriculum was designed based on the six structured inventive thinking (SSIT) approach that can facilitate the development of the knowledge of STEAM content and investigate the perceptions of STEAM subjects by middle school students. The participants in the study were sixty-eight grade 7 students from a middle school in Seoul, Korea. Employing a quasi-experimental research design, the participants were measured on their STEAM knowledge and perceptions before and after participation. The findings indicate that students who participated in global climate change monitoring activities reported gains in their STEAM content knowledge and showed an improvement in their perceptions of STEAM subjects. The latter finding was more pronounced for female students who had significantly higher science achievement and positive perceptions of the STEAM program than for male students. The results of this study suggest that carefully designed projects comprised of SSIT-based environmental activities can be effective in STEAM education at the middle school level.